Mating and immunity in invertebrates. - Lawniczak, M; Barnes, A; Linklater, JR; Boone, J; Wigby, S; Chapman, T (2007)
Mating and immunity are intimately linked to fitness. In both vertebrates and invertebrates, recent investigations into mate choice for immunity, tradeoffs between reproduction and immunity, and the relationships between post-mating processes and immune function have revealed that mating and immunity are also intimately linked to each other. Here, we focus on invertebrates and critically examine the evidence that immunity is under sexual selection, both pre- and post-mating, and explore other hypotheses linking mating and immunity. We find little evidence for a consensus regarding which theories best account for the accumulating empirical data. However, we suggest that progress can quickly be made by exploiting the intrinsic strengths of invertebrate model systems.